2016
DOI: 10.5152/ucd.2015.3125
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection for colorectal diseases: short-term outcomes of a single center

Abstract: Laparoscopic resection for colorectal diseases: short-term outcomes of a single center INTRODUCTIONLaparoscopic colorectal surgery provides less postoperative pain, better cosmesis, shorter hospital stay and earlier patient mobilization (1, 2). Jacobs et al. (3) performed the first laparoscopic colon resection in 1991 (3). However, it took time to be adopted due to its technical difficulties, lack of clinical evidence, the learning curve and fear of tumor seeding (4, 5). The recently published case series prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…6,7 Ancak açık cerrahiye göre birçok avantajı mevcut olup bunların başında kozmetik görünüm, erken derlenme, postoperatif dönemde daha az ağrı olması, yara yeri enfeksiyonunun daha az olması ve insizyonel herni oranının daha az olması gibi faktörler gelmektedir. 8,9 Malignite olgularına bakıldığında sağ kalım için günümüzde kabul edilen en önemli kriterlerin başında diseke edilen lenf nodu sayısının yeterli olması, piyes sınırlarının ve radyal sınırların tümörden temizlenmiş olması gelmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…6,7 Ancak açık cerrahiye göre birçok avantajı mevcut olup bunların başında kozmetik görünüm, erken derlenme, postoperatif dönemde daha az ağrı olması, yara yeri enfeksiyonunun daha az olması ve insizyonel herni oranının daha az olması gibi faktörler gelmektedir. 8,9 Malignite olgularına bakıldığında sağ kalım için günümüzde kabul edilen en önemli kriterlerin başında diseke edilen lenf nodu sayısının yeterli olması, piyes sınırlarının ve radyal sınırların tümörden temizlenmiş olması gelmektedir.…”
Section: Discussionunclassified
“…Attaallah ve ark. 7 yaptıkları çalışmada ise 33 hastada ortalama hastanede yatış süresini 5 gün olarak saptamışlardır. Bizim ortalamamızı arttıran sebeplerden birisinin 3 adet majör komplikasyonlu hastamızın olduğunu düşünmekteyiz.…”
Section: Discussionunclassified
“…Advanced laparoscopic surgery has been used safely in many procedures recently but it is still not considered as the gold standard in colorectal surgery. 6,7 One of the probable reasons for this is the fact that the learning curve is long and steep. 5 The laparoscopic colorectal surgery, which is known to have more advantages than open surgery, provides significant benefit in obese, high ASA score and old patients.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy is being widely used in the treatment of both malign and benign colorectal diseases in many surgical centers where were advanced in laparoscopic procedures. [7,12,13] Previous research has demonstrated its advantages when compared with open surgery, such as short hospital stay, greater satisfaction with incision cosmesis, oncological equivalence, postoperative recovery time, and cost effectiveness. [9,[13][14][15][16] The complication rate of laparoscopic colorectal procedures were reported as 1.5-36% and is not higher than open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[7,12,13] Previous research has demonstrated its advantages when compared with open surgery, such as short hospital stay, greater satisfaction with incision cosmesis, oncological equivalence, postoperative recovery time, and cost effectiveness. [9,[13][14][15][16] The complication rate of laparoscopic colorectal procedures were reported as 1.5-36% and is not higher than open surgery. [2,17] Our complication rate was 21.4% and the most common complication in our series was anastomotic leakage (AL) (7.1%).…”
Section: Discussionmentioning
confidence: 99%